Challenges to knowledge translation in the digital age - Presado, Maria Helena (2022)
The translation of knowledge into clinical practice and behavior change is a slow process that involves the involvement of all stakeholders in the process. Knowledge transfer (CT) is a complex process and encompasses more than the dissemination or communication of research results. Inherent in the pandemic context, our experience reveals some constraints on multidisciplinary and interinstitutional work, but the use of digital platforms can promote communication between academia and practice. Digital technologies pose several challenges to teachers, health professionals and researchers for an evidence-based practice (EBP) and allows us to infer that CT is influenced by the virtual world. We aim to reflect the role of teachers, researchers and clinicians in knowledge transfer in the virtual world, analyze challenges and debate strategies that ensure knowledge transfer. In this sense, we present in this chapter examples of practical cases, contributions and limitations for the use of the online method/technique, reflection of the digital experience. Teaching EBP in school curricula at various levels of education and involving students in projects can be a challenge to the learning process of critical thinking in clinical practice and to the use of online models and techniques, due to the ease of use of technological resources by generations younger. In the Final Considerations, we emphasize the need for a collaborative approach between researchers, clinicians and clients where each takes an active role. The new technologies applied to health and the demands of consumers, force the change of practices and models of organization of services, as well as the need for institutional partnerships.   Keywords: Translational Medical Research Evidence-Based Practice; Health Information Systems; Digital Technology; Health Personnel